2000
DOI: 10.1002/(sici)1520-6327(200001)43:1<9::aid-arch2>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland proteins of the mosquito Culex quinquefasciatus

Abstract: Several properties of the salivary glands of Culex quinquefasciatus mosquitoes were analysed. The amount of protein in female salivary glands increased from 0.26 microg on day one after emergence to about 1.4 microg on day seven. The major polypeptides found in the female salivary glands had molecular weights of 35.7, 28.3, and 20.5 kDa. Antibodies produced by mice immunized by bites of Culex quinquefasciatus female mosquitoes reacted with the 35.7 and 28.3 kDa polypeptides, showing that these molecules were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
(26 reference statements)
3
8
0
1
Order By: Relevance
“…These values are consistent with the morphological differences observed between the salivary glands of males and females. These morphological and protein content differences have been observed in other mosquito species and were related with the different feeding habits of males and females 18,21,24,25 . Females feed on both sugar and blood, whereas males feed on sugar only 43 .…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…These values are consistent with the morphological differences observed between the salivary glands of males and females. These morphological and protein content differences have been observed in other mosquito species and were related with the different feeding habits of males and females 18,21,24,25 . Females feed on both sugar and blood, whereas males feed on sugar only 43 .…”
Section: Discussionsupporting
confidence: 57%
“…darlingi 23 and Cx. quinquefasciatus 25 , demonstrated accumulation preferentially in the distal region and proximal region of the lateral lobes, respectively. The salivary apyrase and alpha-glucosidase of An.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar difference in lobe size of salivary glands has been observed mosquito females, which exhibit three lobes of different sizes (43,44). Moreover, the results show a decrease in gland size between these two species of Lutzomyia post blood feeding in comparison with sugar solution feeding.…”
Section: Resultssupporting
confidence: 78%
“…Aedes aegypti (Champagne et al 1995b), Anopheles (Arca et al 1999) and Culex mosquitoes ( Fig. 1e) (Nascimento et al 2000) present in their saliva apyrases from the same family of 5'-nucleotidases. A novel apyrase enzyme sequence was found recently in the salivary glands of the haematophagous bed bug Cimex lectularius (Valenzuela et al 1998) and homologous sequences were found in the sand flies Lutzomia longipalpis (Charlab et al 1999) and Phlebotomus papatasi , indicating that this family of enzymes is widespread among arthropod species (Fig.…”
Section: Platelet Aggregationmentioning
confidence: 99%